Islamic Activism and Habermas' Theory of Strategic Action: a Case of Parade Tauhid in Jakarta - Siddiq, Akhmad (DINIKA : Academic Journal of Islamic Studies, 2016)
Capturing the case of Parade Tauhid in Indonesia, this paper aims to describe embodied relationship between religion (Islam) and politics. As part of social action, Islamic activism provides variety of contention which is practiced in the name of “Islam”: ideologically, structurally, and purposely. Within his explanation of communicative action theory, Habermas acknowledges what so-called as “strategic action” which can be defined as every action oriented to success under the aspect of rational choice and assess the efficacy of influencing decisions or positions of rational opponent. In this context, Parade Tauhid is perceived to be conducted for reaching several political and theological purposes based on rational choices, although it is practiced by performing religious event. This paper attempts to describe definition of Islamic activism, explore the event of Parade Tauhid, and analyze the parade using Habermas’s theory of strategic action.